1988
DOI: 10.1007/bf00442029
|View full text |Cite
|
Sign up to set email alerts
|

Hydrographic patterns in McMurdo Sound, Antarctica and their relationship to local benthic communities

Abstract: Summary. Measurements of hydrographic parameters (temperature, salinity, nitrate, nitrite, phosphate, chlorophyll a, phaeophytin, and oxygen) in McMurdo Sound, Antarctica during spring, 1984, before the regional phytoplankton bloom, and summer, 1984, after the peak of the bloom, indicate the several processes contribute to changes in the vertical and horizontal structure of the water column. Regional variation in the source of water masses within the Sound, ice cover patterns, and meltwater from the Ross Ice S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 43 publications
(57 reference statements)
10
92
1
Order By: Relevance
“…and Wadhams, 1989). In the austral winters of 1984, Barry (1988 and Crocker and Wadhams ( 1989) respectively reported that, prior to basal melting, the locations of the thickest platelet-ice accumulations corresponded to the areas of maximum surface supercooling reported by Lewis and Perkin (1985). The pattern of occurrence and quantity of platelet ice in our…”
Section: Upper Congelation Ice Layersupporting
confidence: 55%
“…and Wadhams, 1989). In the austral winters of 1984, Barry (1988 and Crocker and Wadhams ( 1989) respectively reported that, prior to basal melting, the locations of the thickest platelet-ice accumulations corresponded to the areas of maximum surface supercooling reported by Lewis and Perkin (1985). The pattern of occurrence and quantity of platelet ice in our…”
Section: Upper Congelation Ice Layersupporting
confidence: 55%
“…Our sampling sites were located about 10 to 25 km west of Ross Island. The current at our sampling sites consistently came from the north; thus we were likely sampling water recently advected into the region from the southwestern Ross Sea (Barry 1988). Although we will discuss our findings in terms of a seasonal trend it is important to note that we did not follow the same water mass throughout the study.…”
Section: Materals and Methodsmentioning
confidence: 90%
“…By 10 January macrocolony abundance and cell size were both greatly decreased as the alga apparently entered a different part of its life cycle. It is not clear what environmental factor causes the change in morphology and presumably growth rate, since concentrations of major nutrients remain high and temperature fluctuations in McMurdo Sound are small during this period (Littlepage 1965, Barry 1988.…”
Section: Seasonal Patterns Of Bacterial Abundance and Sizementioning
confidence: 99%
“…While sea ice algal productivity in McMurdo Sound may be high (Palmisano and Sullivan 1983), its contribution through detrital fallout to benthic systems is poorly understood (Dayton 1990). During summer Phaeocystis blooms, the eastern sound receives plankton-rich waters, which flow southward from the Ross Sea, while the western sound is subject to relatively plankton-poor waters that flow northward after circulating under the Ross Ice Shelf (Barry andDayton 1988, Grebmeier and. The locations we sampled encapsulated the variability in the strong east-west and north-south gradients in different potential food sources and productivity in the high latitude waters of the southwestern Ross Sea coast.…”
Section: Study Area and Speciesmentioning
confidence: 99%